Childhood trauma, psychosis liability and social stress reactivity: a virtual reality study. Issue 16 (13th September 2016) - Veling, W.; Counotte, J.; Pot-Kolder, R.; van Os, J.; van der Gaag, M.
Abstract : Background: Childhood trauma is associated with higher risk for mental disorders, including psychosis. Heightened sensitivity to social stress may be a mechanism. This virtual reality study tested the effect of childhood trauma on level of paranoid ideations and distress in response to social stress, in interaction with psychosis liability and level of social stress exposure. Method: Seventy-five individuals with higher psychosis liability (55 with recent onset psychotic disorder and 20 at ultra-high risk for psychosis) and 95 individuals with lower psychosis liability (42 siblings and 53 controls) were exposed to a virtual café in five experiments with 0–3 social stressors (crowded, other ethnicity and hostility). Paranoid ideation was measured after each experiment. Subjective distress was self-rated before and after experiments. Multilevel random regression analyses were used to test main effects of childhood trauma and interaction effects. Results: Childhood trauma was more prevalent in individuals with higher psychosis liability, and was associated with higher level of (subclinical) psychotic and affective symptoms. Individuals with a history of childhood trauma responded with more subjective distress to virtual social stress exposures. The effects of childhood trauma on paranoia and subjective distress were significantly stronger when the number of virtual environmental stressors increased. Higher psychosis liability increased the effect of childhood trauma on peak subjective distress and stress reactivity during experiments. Conclusions: Childhood trauma is associated with heightened social stress sensitivity and may contribute to psychotic and affective dysregulation later in life, through a sensitized paranoid and stress response to social stressors.